Análisis de los consumos históricos de agua potable en el cantón de Santo Domingo - Richard Santiago, Reino Pacheco (2022)
ABSTRACT The demand for drinking water in Ecuador has been increasing due to various sociodemographic factors, water quality, and socioeconomic and climatological conditions, influencing the provided service to the population. These factors influence consumption variations because the recommended endowments of the CPE INEN 005-9- 1 standard (1992) need to be clarified, and there are no data from existing system studies. The recommendation of the regulation to improve the endowments in the future designs for potable water is to carry out specific studies for each city. This research analyzes the residential historical records of monthly drinking water consumption in the Santo Domingo canton between 2018 and 2020, provided by the “Empresa Pública Municipal de Agua Potable y Alcantarillado Santo Domingo” (EPMAPA-SD). The methodology follows a structured process focusing on quantitative by the type of obtained information. The delivered data, which we refer to as raw ones, went through a manual elimination process and later a statistical debugging through the Minitab software using Boxplot and Whiskers. Then the 1 350 137 of valid data were exposed to the normality test, homoscedasticity, Analysis of variance, Tukey test, Interval plots, and descriptive diagrams as part of the statistical Analysis to determine maximum consumption and the historical consumption average, and finally the coefficient of variation was calculated of daily consumption (Kd). The maximum consumption of 18.39 m3 in May 2020 coincides with the second most crucial mandatory confinement by Covid-19. A historical average of 16.84 m3 results in a coefficient Kd = 1.09, below the range of 1.3 to 1.5 of the regulations. Compared with populations close to the city that has already been studied and other featured populations (see Table 2), it is concluded that the larger the population, the coefficient of variation (Kd) value will be less. Keywords: Demand for drinking water, sociodemographic factors, water quality, recommended endowments, and coefficient (Kd). Firmado electrónicamente por: DANILO RENEE YEPEZ OVIEDO Reviewed by: Danilo Yépez Oviedo English professor UNACH 0601574692